The Kinetics of Aragonite Formation from Solution via Amorphous Calcium Carbonate - Simon M. Clark; Vili Grigorova; Bruno Colas; Tamim A. Darwish; Kathleen Wood; Joerg Neuefeind; Dorrit E. Jacob (Nanomaterials, 2022)
Magnesium doped Amorphous Calcium Carbonate was synthesised from precursor solutions containing varying amounts of calcium, magnesium, H2O and D2O. The Mg/Ca ratio in the resultant Amorphous Calcium Carbonate was found to vary linearly with the Mg/Ca ratio in the precursor solution. All samples crystallised as aragonite. No Mg was found in the final aragonite crystals. Changes in the Mg to Ca ratio were found to only marginally effect nucleation rates but strongly effect crystal growth rates. These results are consistent with a dissolution-reprecipitation model for aragonite formation via an Amorphous Calcium Carbonate intermediate.